2015
DOI: 10.1063/1.4914393
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation of a generation-recombination center with a deep level trap in GaN

Abstract: Articles you may be interested inDeep levels in as-grown and electron-irradiated n-type GaN studied by deep level transient spectroscopy and minority carrier transient spectroscopy J. Appl. Phys. 119, 095707 (2016)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 17 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Measurement was performed in a temperature range between 25 and 150˝C using a heated plate and an ATT Systems A150 temperature controller. (e.g., [14,17,20,21]) and between 0.71 and 0.82 eV (e.g., [1,9,19,[22][23][24]) were the most commonly reported. Unfortunately, their origin remains ambiguous.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement was performed in a temperature range between 25 and 150˝C using a heated plate and an ATT Systems A150 temperature controller. (e.g., [14,17,20,21]) and between 0.71 and 0.82 eV (e.g., [1,9,19,[22][23][24]) were the most commonly reported. Unfortunately, their origin remains ambiguous.…”
Section: Methodsmentioning
confidence: 99%
“…The most popular one is deep-level transient spectroscopy (DLTS), which can be performed in capacitance-mode (C-DLTS) [7][8][9] or current-mode (I-DLTS) [10][11][12]. However, capacitance or current transient measurement on real HFET devices can be limited to a degree because of their small dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…These results match roughly with previous literatures. [25][26][27][28] Deep level traps were induced in the near-interface of SiN X /AlGaN during electrical stress. The results are summarized in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature-dependent relationship was also re-plotted in figure 4(c). It was found that the emission time constant maintained an exponential relationship with temperature, which can be fitted by the Arrhenius relation, assuming a degeneracy ratio of 1, as shown in equation ( 2) [38]:…”
Section: Dlts Results and Discussionmentioning
confidence: 99%